Pengaruh Penggunaan Media Pembelajaran Articulate Storyline Terhadap Hasil Dan Minat Belajar Peserta Didik - j, Winaldi; Ahsan, Muhammad; Usman, Muhammad; Misbahuddin (Journal of Mathematics Learning Innovation, 2023)
This research aims to find out whether there is an influence of using articulate storylines on students' learning outcomes and interest. The approach used is a quantitative approach with a quasi experimental design research type in the form of a nonequvalent control group design. The population in this study was class XI of SMAN 5 Soppeng, totaling 206 students. By using a simple cluster random sampling technique, class XI.2 was chosen as the control class whose learning used conventional methods and class XI.6 as the experimental class whose learning used articulate storyline media. Data on learning outcomes was obtained through tests, while data on interest in learning was obtained through questionnaires. The data analysis used is descriptive and inferential statistical analysis. From this research it was found that (1) the use of Articulate Storyline media in learning was carried out very well. (2) there is a better or increased influence on the learning outcomes and interest of students who use Articulate Storyline media compared to using conventional learning, (3) there is an influence of using Articulate Storyline media on students' learning outcomes and interest as proven by the MANOVA test with values significance is 0.00 which is below the value of 0.05.